Factors that Influence the Potential of Street Vendors to Gain Access to Bank Loans in Balikpapan - Mangawing, Lefi Adiba (Journal of Social Research, 2023)
One of the forms of the informal sector is street vendors, and they unknowingly possess numerous potentials and uncounted benefits that could significantly contribute to Indonesia's economy. The purpose of this research is to analyze the factors influencing street vendors' access to support from banks. Conducted in Balikpapan, East Kalimantan, this quantitative study utilizes primary data collected through distributed questionnaires, specifically targeting starch-dough fried street vendors. The analysis method employed in this research includes descriptive and factor analysis, which was performed using SPSS version 29. The findings reveal three new factors that hold significant influence and present fresh perspectives for street vendors seeking support. These factors are (1) awareness of street vendor formalization, (2) development of street vendors, and (3) prejudice towards vendor association. The research results indicate that the predictive ability of all independent variables as new perspectives for street vendors amounts to 56.275%. However, it is worth noting that the remaining 43.725% is affected by other variables that have not been taken into account within this particular study. In conclusion, this research highlights the importance of recognizing and tapping into the potential of street vendors, as well as understanding the factors that can help them access support from financial institutions for their economic growth and development.